The Gospel of John in modern interpretation - Porter, Stanley E.; Fay, Ron C. (Milestones in New Testament scholarship, 2018)
"The Gospel of John in Modern Interpretation provides a unique look at the lives and work of eight interpreters who have significantly influenced Johannine studies over the last two centuries. The chapters contain short biographical sketches of the scholars that illuminate their personal and academic lives, followed by summaries and evaluations of their major works, and concluding with an analysis of the ongoing relevance of their work in contemporary Johannine scholarship. Key thinkers surveyed include C.H. Dodd, Rudolph Bultmann, Raymond Brown, Leon Morris, and R. Alan Culpepper. An introduction and conclusion by general editors Stanley Porter and Ron Fay trace the development of Johannine scholarship from F.C. Baur to the present, and examine how these eight scholars' contributions to Johannine studies have shaped the field. Anyone interested in the recent history of the study of John will find this volume indispensable."--